Examining the crime prevention claims of crime prevention through environmental design on system-trespassing behaviors: a randomized experiment - Berenblum, Tamar (2021)
Crime prevention through environmental design (CPTED) is a non-punitive method for reducing crime through the design of the built environment. The relevance of CPTED strategies however is less clear in the context of computing environments. Building upon prior research indicating that computing environments may change computer users’ behaviors, this study tests the effectiveness of CPTED based approaches in mitigating system trespassing events. Findings from this randomized controlled field trial demonstrate that specific CPTED strategies can mitigate hacking events by: reducing the number of concurrent activities on the target computer, attenuating the number of commands typed in the attacked computer, and decreasing the likelihood of hackers returning to a previously hacked environment. Our findings suggest some novel and readily implemented strategies for reducing cybercrime